Significados do lazer no período da pandemia: um estudo com estudantes de educação física da Universidade Federal do Pará-Belém - COSTA, Gustavo dos Santos (2022)
This research belongs to the project “Experiences and Barriers of Leisure in times of pandemic: A study with students from the College of Physical Education – Universidade Federal do Pará - Campus Belém”. The purpose of this study was to analyze the answers of students in the Graduation in Physical Education, as to the meanings of leisure during the social distance resulting from the Covid-19 pandemic. The research approached quantitatively and qualitatively the answers to a structured questionnaire with closed and some open questions, answered by 82 students. From the data obtained, were divided into three categories: “Leisure and Health/Mental Health”; “Leisure how Entertainment/Distraction” and “Leisure and Escapism”. It is concluded that Leisure contributed to the keeping of mental health/health, in addition to instituting new forms of social relationships, consumption of cultural content and also allowed the escape from reality and problems arising from the pandemic.